2022
DOI: 10.9734/ijbcrr/2022/v31i9780
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Contamination Index, Metal Index and Polycyclic Aromatic Hydrocarbon Content of Ochani River in Ogoni, Rivers State, Nigeria

Abstract: The Heavy metal Pollution Index (HPI), Metal Index (MI) and the Polycyclic Aromatic Hydrocarbon (PAH) contents of crude oil-polluted Ochani River in Ejamah-Ebubu community were investigated using physicochemical properties, Heavy Metal Analytic Method (AAS), GC-MS method and heavy metal pollution model. The results showed that Ochani River sampling station 2 (ORPS 2) had highest values of temperature, conductivity, turbidity, total solid (TS), total dissolved solid (TDS), Total Suspended Solid (TSS), Dissolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…International standards for heavy metal pollution and their application in Nigeria have been a topic of concern in several studies. The studies have focused on different aspects of heavy metal pollution, including its effects on water sources, staple food cultivars, drinking water, and soil (Nicholas et al, 2022;Agbaje et al, 2023). The results of these studies have shown that heavy metal concentrations in various environmental samples often exceed the recommended limits set by international standards such as those of the World Health Organization (WHO) and the Standard Organization of Nigeria.…”
Section: Ogbeide O; Henry Bmentioning
confidence: 99%
See 1 more Smart Citation
“…International standards for heavy metal pollution and their application in Nigeria have been a topic of concern in several studies. The studies have focused on different aspects of heavy metal pollution, including its effects on water sources, staple food cultivars, drinking water, and soil (Nicholas et al, 2022;Agbaje et al, 2023). The results of these studies have shown that heavy metal concentrations in various environmental samples often exceed the recommended limits set by international standards such as those of the World Health Organization (WHO) and the Standard Organization of Nigeria.…”
Section: Ogbeide O; Henry Bmentioning
confidence: 99%
“…This indicates a potential health risk to human populations and ecosystems. Overall, research from Nigeria highlights the importance of adhering to international standards to protect human health and the environment from the adverse effects of heavy metal pollution (Adeyeye et al, 2018;Afonne et al, 2022;Essien et al, 2022;Nicholas et al, 2022;Agbaje et al, 2023). International standards for heavy metal pollution also involve conventions, protocols, and agreements aimed at reducing and controlling the release of heavy metals into the environment.…”
Section: Ogbeide O; Henry Bmentioning
confidence: 99%
“…The containers were thoroughly washed, sterilized with 70% ethanol, rinsed multiple times with distilled water, and finally with the sample solution before collecting the sample for analysis. The collection of the crude oil-polluted water sample from Ochani River followed the procedure reported by Nwogu et al (2022). The water sample was collected with a 2-liter plastic cup at a depth of 8 -10 cm and then transferred into a 25-liter container with screw cap, labeled appropriately.…”
Section: Collection Of Water Samplementioning
confidence: 99%
“…The unrelenting organic pollutant such as polycyclic aromatic hydrocarbons (PAHs) is a hazard that has to be curbed as it has dented every part of the ecosystem. This PAHs are mostly obtained from human endeavors or inherent processes (Hahladakis et al, 2013;Nwogu et al, 2022). The increase in PAH discharge as a consequence of partial incineration from human activities allows its deposition in the soil, which has led to its accumulation in food crop and other biota, and is then transferred to humans through the food chain (Kim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These water bodies serve as water sources to the locals occupying the area and it usually provides for activities, such as drinking, farming, etc. (Nwogu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%